IMPLEMENTASI GOOD CORPORATE GOVERNANCE DI INDONESIA - Wibowo, Edi (Universitas Slamet Riyadi, 2010)
ABSTRAK Applying good corporate governance becoming become strategic determinant to company so that earning ever improve value and also look after going concern growth process. For the reason, every company requires to continue to improve its hard work so that can take benefit from applying good corporate governance. If this good corporate governance principle is executed seriously, may simply company will have sturdy base in running its business. Externally, company will be more be trusted by investor, meaning its stocks market value will increasingly. Partner work even also does not hesitate to develop broader business relation again. Supplier have trustworthy and clear hold and also sure will be treated fairly so that can give best price, which mean create efficiency to company. Creditors even also have high trust for the giving of its credit which is possible needed to extension of is effort. Keywords: Good corporate governance, fairness, transparency, accountability, and responsibility